2019
DOI: 10.1002/smr.2199
|View full text |Cite
|
Sign up to set email alerts
|

A systematic mapping study on crowdsourced requirements engineering using user feedback

Abstract: Crowdsourcing is an appealing concept for achieving good enough requirements and just-in-time requirements engineering (RE). A promising form of crowdsourcing in RE is the use of feedback on software systems, generated through a large network of anonymous users of these systems over a period of time. Prior research indicated implicit and explicit user feedback as key to RE-practitioners to discover new and changed requirements and decide on software features to add, enhance, or abandon.However, a structured ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Text mining tools: focus on analyzing available data without actively involving stakeholders. Thereby not supporting elicitation directly, rather, they determined the relevance and importance of a sentence or statement through natural language algorithms, usually based on app store reviews [32], [33], [34]. Hosseini et al [35] surveyed experts to support the use of crowdsourcing for the help of requirements elicitation.…”
Section: B Crowdsourcing-based Requirements Engineeringmentioning
confidence: 99%
“…Text mining tools: focus on analyzing available data without actively involving stakeholders. Thereby not supporting elicitation directly, rather, they determined the relevance and importance of a sentence or statement through natural language algorithms, usually based on app store reviews [32], [33], [34]. Hosseini et al [35] surveyed experts to support the use of crowdsourcing for the help of requirements elicitation.…”
Section: B Crowdsourcing-based Requirements Engineeringmentioning
confidence: 99%
“…Axial coding refers to the formation of the main category after the analysis and induction of the initial category obtained by the open coding. The 15 initial categories obtained by open coding are analyzed and summarized here before according to the definition of user needs in software engineering (Wang et al, 2019 ): (1) The conditions or capabilities required by the user to solve problems or achieve goals; (2) The capabilities of system and its component to meet the requirement from contracts, standards, specifications or other formal documents; (3) A document description that reflects the conditions or capabilities described in the above two scenarios, which mainly includes functional requirements and non-functional requirements. According to various needs of WeChat in different operating systems, we get a theoretical system composed of 6 main categories, namely 6 user needs of WeChat APP users obtained by Grounded Theory, which are: performance, reliability, usability, functional deficiency, functional insufficiency and system adaptability.…”
Section: Data Preparationmentioning
confidence: 99%
“…Wang et al 16 conducted an SLR on crowdsourced user feedback used for RE purpose. The authors considered 44 studies as their primary study set to know how user feedback empowered RE activities.…”
Section: Related Workmentioning
confidence: 99%
“…Bakar et al 15 have surveyed 13 studies that mainly focus on how product descriptions and software requirements specification (SRS) document are used to elicit user requirements for software product line organizations. Wang et al, 16 Groen et al, 17 and Mao et al 18 have surveyed literature that emphasizes on crowdsourcing (e.g., from App Store and Google Play Store) and RE. The authors have concluded that user feedback can be a major source to support RE activities.…”
Section: Introductionmentioning
confidence: 99%